Aminothiazolones as potent, selective and cell active inhibitors of the PIM kinase family. Issue 22 (15th November 2020) - Quevedo, Camilo E.; Bataille, Carole J.R.; Byrne, Simon; Durbin, Matthew; Elkins, Jon; Guillermo, Abigail; Jones, Alan M.; Knapp, Stefan; Nadali, Anna; Walker, Roderick G.; Wilkinson, Isabel V.L.; Wynne, Graham M.; et al.
Graphical abstract: Abstract: We have previously reported the discovery of a series of rhodanine-based inhibitors of the PIM family of serine/threonine kinases. Here we described the optimisation of those compounds to improve their physicochemical and ADME properties as well as reducing their off-targets activities against other kinases. Through molecular modeling and systematic structure activity relationship (SAR) studies, advanced molecules with high inhibitory potency, reduced off-target activity and minimal efflux were identified as new pan-PIM inhibitors. One example of an early lead, OX01401, was found to inhibit PIMs with nanomolar potency (15 nM for PIM1), inhibit proliferation of two PIM-expressing leukaemic cancer cell lines, MV4-11 and K562, and to reduce intracellular phosphorylation of a PIM substrate in a concentration dependent manner.